Space-time Characteristics of 16 PM2.5-bound Phthalates (PAEs) in Ambient Air from Shanghai: Profiles, Sources, Meteorological Effects, and Exposure Risks - Janvier Munyaneza; Md Faysal Hossain; Qilong Jia; Yusen Duan; Guangli Xiu (Aerosol and Air Quality Research)
Abstract Generated by chemical combinations between alcohols and phthalic anhydrites, phthalates are a group of synthetic chemicals broadly utilized as plasticizers. They occur in both particle and gas phases in the air causing threats to human health. In the study in hands, LC-MS/MS was employed for the analysis of PM2.5-PAEs in 128 ambient PM2.5 samples from nine locations (urban, sub-urban and coastal) in Shanghai between February 2015 and September 2021. Six PAE congeners, namely di-n-butylphthalate (DBP), dimethylphthalate (DMP), diisononylphthalate (DINP), di-2-ethylphthalate (DEP), diisobutyl phthalate (DIBP) and di (2-propylheptyl) phthalate (DPHP), which are grouped as (Σ6PAEs) were the most profuse species (with detection frequency (DF) ranging from 44.5% to 85.9%), with concentrations ranging between 26.85 (DEP) to 1840 ng m−3 (DIBP). Two congeners (DBP and DIBP) contributed significantly (79.4%) to the overall concentration of PAEs in the campaign, and exhibited a strong positive correlation (Spearman: r = 0.876, p < 0.05). Densely populated sites and those situated in periphery of manufacturing areas seemed to exhibit higher mean concentrations of Σ6PAEs. Daily mean and median concentrations comprising all the species (Σ16PAEs) were generally higher in samples collected during colder periods (38.3 and 37.5 ng m−3, respectively) rather than within samples gathered in warmer periods (31 and 26.9 ng m−3, respectively), though there wasn’t a statistically significant difference between mean concentrations for both periods (ANOVA: p > 0.05, F stat. < F critical). Statistically significant correlations were found between temperature and concentrations of both DBP and Σ16PAEs (p < 0.05, r = 0.34 and 0.35, respectively). Among population groups, an elevated daily intake (EDI) ranging from 1.04 to 27.95 ng kgBWt−1 day−1 was found for toddlers, with the highest estimated hazard index of 1.5 × 10−2.